Inside Back Cover: Facile Construction of g‐C3N4 Nanosheets/TiO2 Nanotube Arrays as Z‐Scheme Photocatalyst with Enhanced Visible‐Light Performance (ChemCatChem 19/2016). Issue 19 (6th October 2016) - Zhou, Dantong; Chen, Zhi; Yang, Qian; Shen, Cai; Tang, Gao; Zhao, Shilong; Zhang, Jingji; Chen, Da; Wei, Qinhua; Dong, Xiaoping
Abstract : The Cover shows a Z‐scheme g‐C3 N4 nanosheets/TiO2 nanotube array photocatalyst. In their Full Paper, D. Zhou et al. successfully loaded graphitic carbon nitride nanosheets on the TiO2 nanotube arrays (TNTAs) by a facile immobilization method. The visible‐light‐driven Z‐scheme g‐C3 N4 NSs/TNTAs photocatalyst has been prepared by simply dispersing g‐C3 N4 NSs into the electrolyte during the in situ anodization. The colored dye Rhodamine B (Rh B) and colorless antibiotic agent tetracycline hydrochloride (TC‐HCl) can be effectively degraded on this photocatalyst under visible light irradiation. The all‐solid‐state Z‐scheme g‐C3 N4 NSs/TNTAs displayed enhanced visible light photocatalytic activity and good stability. The paper may introduce new approaches in the design of highly efficient photocatalyst and brings new insight to environmental remediation. More information can be found in the Full Paper by D. Zhou et al. onpage 3064 in Issue 19, 2016 (DOI:10.1002/cctc.201600828 ).